Dispersed phase structure and micro-explosion behavior under different schemes of water-fuel droplets heating. (1st January 2020) - Antonov, Dmitry; Piskunov, Maxim; Strizhak, Pavel; Tarlet, Dominique; Bellettre, Jérôme
Abstract: One of the known and still unsolved problems of internal combustion engines and liquid fuel power plants is the complexity of efficient (i.e. with minimal cost of basic resources: time, energy and raw materials) ignition of fuels issued from valorization of waste. A promising way to improve the efficiency of ignition of liquid fuels is a secondary atomization using the micro-explosion of water-fuel droplets. This phenomenon is called micro-explosion when concerning an individual water-in-oil emulsion drop among the combusting spray. This process dramatically accelerates fuel heating and ignition, since fuel droplets issued from the secondary atomization are smaller and faster, increasing interfacial area. To investigate the atomization efficiency and its causes, the present work quantifies the occurrence of successful micro-explosion under large samples of experimental data. The behavior of water-fuel drops in the form of fine, middle-size emulsions or two immiscible liquids is observed using schemes with conductive, convective or radiative heat transfer provided at the same range of temperature.